2017
DOI: 10.3389/fnagi.2017.00042
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Cognitive Functioning in Healthy Seniors with a Technology-Based Foreign Language Program: A Pilot Feasibility Study

Abstract: Researchers have hypothesized that learning a foreign language could be beneficial for seniors, as language learning requires the use of extensive neural networks. We developed and qualitatively evaluated an English training program for older French adults; our principal objective was to determine whether a program integrating technology is feasible for this population. We conducted a 4-month pilot study (16, 2-h sessions) with 14 French participants, (nine women, five men, average age 75). Questionnaires were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(123 citation statements)
references
References 57 publications
9
109
0
Order By: Relevance
“…Pfenninger and Polz (2018) found that personal motivation, self-study effort, learning progress and social aspects appeared to be co-dependent at least for some participants; it thus makes sense to include (psychometric) tests that probe the learners' environment, history and personality. A similar picture emerged in Ware et al (2017), who conducted a four-month pilot study (16 two-hour sessions) with 14 French participants: five beginners, five intermediate, and four advanced learners of L2 English. Three measuressemi-structured qualitative interviews, the Montreal Cognitive Assessment (MoCA) test and the University of California Loneliness Assessment (UCLA) scalewere administered before and after a technology-based intervention to measure cognitive level and feelings of loneliness or isolation.…”
Section: How Older Adults May Benefit From L2 Learningmentioning
confidence: 60%
“…Pfenninger and Polz (2018) found that personal motivation, self-study effort, learning progress and social aspects appeared to be co-dependent at least for some participants; it thus makes sense to include (psychometric) tests that probe the learners' environment, history and personality. A similar picture emerged in Ware et al (2017), who conducted a four-month pilot study (16 two-hour sessions) with 14 French participants: five beginners, five intermediate, and four advanced learners of L2 English. Three measuressemi-structured qualitative interviews, the Montreal Cognitive Assessment (MoCA) test and the University of California Loneliness Assessment (UCLA) scalewere administered before and after a technology-based intervention to measure cognitive level and feelings of loneliness or isolation.…”
Section: How Older Adults May Benefit From L2 Learningmentioning
confidence: 60%
“…Van der Hoeven and de Bot (2012) claim that older adults can relearn apparently forgotten lexemes just as well as younger ones, while according to Bahrick (1984) an individual may retain, at least as a dormant feature, most second-language knowledge for decades, even without using it. In Ware et al (2017)'s study, however, even those informants who had previously learned the target language (henceforth TL) sometimes found it hard to memorise new vocabulary, which may be rather demotivating. On the other hand, facing a complex task such as learning a novel language could be mentally stimulating for elderly people.…”
Section: Old Age and Language Learningmentioning
confidence: 89%
“…Potentially fruitful interventions in cognitive as well as social stimulation can be based on FL teaching (Ware et al, 2017) since the development of linguistic skills can enhance resistance to cognitive impairment. Conversely, the presence of dementia or other neurodegenerative conditions has been found to greatly affect linguistic proficiency (Forbes-McKay and Venneri, 2005), thus going to show how language is inextricably intertwined with different aspects of brain functioning.…”
Section: Learning a Foreign Language To Fight Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest to the topic of language learning in the third age dates back to the 1970s (Kalfus, 1977), but first studies were not focused on the individual differences in older adults' ability to acquire a new language. Further case studies, surveys and interviews (Swain & Lapkin, 2011;Lenet et al, 2011;Ware et al, 2017) compared young adults with older adults. The advantages of studying foreign languages in older adults from the point of view of 'cognitive reserve', as well as language learning strategies to attain both general language proficiency and literacy skills were researched by European and American authors (Antoniou et al, 2013;Bialystok et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%